2019
DOI: 10.1371/journal.pone.0220950
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of antioxidant, antibacterial, antidiabetic, and cytotoxicity potential of silver nanoparticles synthesized using the outer peel extract of Ananas comosus (L.)

Abstract: Currently, green nanotechnology-based approaches using waste materials from food have been accepted as an environmentally friendly and cost-effective approach with various biomedical applications. In the current study, AgNPs were synthesized using the outer peel extract of the fruit Ananas comosus (AC), which is a food waste material. Characterization was done using UV–visible spectroscopy, X-ray diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy, scanning electronic micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
76
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(89 citation statements)
references
References 65 publications
12
76
1
Order By: Relevance
“…AgNPs demonstrated a slightly higher MIC and MBC values of 50 and 100 mg ml À1 respectively, against L. monocytogenes. 36 Moreover, a similar observation was recorded earlier where AgNPs synthesized from the aqueous leaf extract of Murraya koenigii exhibited MICs as 32, 16, and 64 mg ml À1 against methicillin-resistant S. aureus (MRSA), E. coli, and ESbLproducing E. coli. 12 In another study, AgNPs synthesized from the extract of Phyla dulcis were found effective against E. coli O157:H7, drug-resistant S. typhimurium, L. monocytogenes and S. aureus.…”
Section: Antibacterial Activity Of Tn-agnpssupporting
confidence: 75%
“…AgNPs demonstrated a slightly higher MIC and MBC values of 50 and 100 mg ml À1 respectively, against L. monocytogenes. 36 Moreover, a similar observation was recorded earlier where AgNPs synthesized from the aqueous leaf extract of Murraya koenigii exhibited MICs as 32, 16, and 64 mg ml À1 against methicillin-resistant S. aureus (MRSA), E. coli, and ESbLproducing E. coli. 12 In another study, AgNPs synthesized from the extract of Phyla dulcis were found effective against E. coli O157:H7, drug-resistant S. typhimurium, L. monocytogenes and S. aureus.…”
Section: Antibacterial Activity Of Tn-agnpssupporting
confidence: 75%
“…A mixture of dried AgCl-NPs and KBr was ground into a fine powder and pressed into a pellet. Using a Nicolet 800 FTIR spectrometer (Nicolet, Madison, USA), absorption spectra of AgCl-NPs included in pellets were acquired at wavelengths ranging from 4000 to 400 cm −1 at resolution of 4 cm −1 , as described by Das et al [24].…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy to mention that traditional chemical reductants implemented in AgNPs synthesis, such as hydrazine, dimethyl hydrazine, NaBH 4 , etc., are environmentally hazardous and will bring potential environmental risks. However, numerous studies have reported the utilization of medicinal plants to synthesize and stabilize metallic nanoparticles, very particularly AgNPs, via the green synthesis method; a method considered to be cost-effective, environment-friendly and easily scaled up for large-scale synthesis of nanoparticles [22][23][24] . Furthermore, this method does not require high pressure, temperature, and energy.…”
mentioning
confidence: 99%